In Vitro Studies Of Antimicrobial Properties Of Extracts From Unani Medicinal Plants - NAMRA H. GHANSAR,; SUPRIYA U. BHOPALE,; VAISHALI S. PRABHUNE, (International Journal of Pharma and Bio Sciences, 2012)
India has been blessed with rich source of medicinal plants that have been used since ages to cure diseases. Unani system of medicine is an ancient system of medicine that relies on natural drugs. Due to the growing problem of multi-drug resistance, skin infections have become very common. The skin pathogens like Staphylococcus aureus, Candida albicans, Pseudomonas aeruginosa and Escherichia coli are responsible for severe skin infections. Unani plants, source of wide range of secondary metabolites possessing antimicrobial properties can be harnessed to treat these pathogens. In this study, twelve plants were assessed for their antimicrobial properties by subjecting them to extraction using various solvents. It was found that methanol extracts of plants exhibited maximum antimicrobial activity against Staphylococcus aureus and Candida albicans. Effect of metals like silver and iron were also studies on methanol extracts of Psoralea corylifolia and Embelia ribes. It was found that combination of silver nitrate with these extracts were effective against Gram negative pathogens.